calculus

posted by Daniel

Find an equation of the tangent line to the curve at

y = cosx - sinx (pi, -1)

I found y'= -sinx - cosx

and used the equation of the tangent
y = mx +b

I input the values and get -1 - [(-sinx - cosx) * pi] = b

the answer says it is y = x - 1 - pi

I have no idea how the answer got that.

  1. bobpursley

    m= -sinPI-cosPI=1
    y= x+b
    -1=PI+b
    b= -PI-1

    y=x-pi-1

Respond to this Question

First Name

Your Answer

Similar Questions

  1. Pre-Calc

    Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 - cosx)/cosx)/((sinx …
  2. Trigonometry.

    ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated side …
  3. Trig........

    I need to prove that the following is true. Thanks (cosx / 1-sinx ) = ( 1+sinx / cosx ) I recall this question causing all kinds of problems when I was still teaching. it requires a little "trick" L.S. =cosx/(1-sinx) multiply top and …
  4. Ap Calc AB

    Find the equation of the line normal to the curve at (0,0). (Normal lines are perpendicular to the tangent lines) 2y + sinx = xcoxy I found the derivative to be (cosy - cosx)/ (2+ xsiny) then the slope tangent is 0...then the slope …
  5. Math - Pre- Clac

    Prove that each of these equations is an identity. A) (1 + sinx + cos x)/(1 + sinx + cosx)=(1 + cosx)/sinx B) (1 + sinx + cosx)/(1 - sinx + cosx)= (1 + sin x)/cosx Please and thankyou!
  6. maths - trigonometry

    I've asked about this same question before, and someone gave me the way to finish, which I understand to some extent. I need help figuring out what they did in the second step though. How they got to the third step from the second. …
  7. Trigonometry Check

    Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] = [cosx-((1)cosx-(0)sinx)sinx]/[cosx-((-1)cosx+(0)sinx)tanx] = [cosx-cosxsinx]/[cosx+cosxtanx] = [cosx(1-sinx]/[cosx(1+tanx] …
  8. Math

    Im really struggling with these proving identities problems can somebody please show me how to do these?
  9. trigonometry

    can i use factoring to simplify this trig identity?
  10. Calculus

    If y=3/(sinx+cosx) , find dy/dx A. 3sinx-3cosx B. 3/(sinx+cosx)^2 C. -3/(sinx+cosx)^2 D. 3(cosx-sinx)/(sinx+cosx)^2 E. 3(sinx-cosx)/(1+2sinxcosx)

More Similar Questions